Assessing Modern Calluna Heathland Fire Temperatures Using Raman Spectroscopy: Implications for Past Regimes and Geothermometry - Theurer, Thomas; Naszarkowski, Noemi; Muirhead, David K.; Jolley, David; Mauquoy, Dmitri (Frontiers in Earth Science, 2022)
Charcoal geothermometry continues to offer considerable potential in the study of palaeowildfires over decadal, centennial, millennial, and deep time scales – with substantial implications for the understanding of modern wildfire intensification. Recent developments in the application of Raman spectroscopy to carbonaceous organic material have indicated its capability to potentially reconstruct the palaeocharcoal formation temperature, and equivalent palaeowildfire pyrolysis intensity. Charcoal reflectance geothermometry (which also relies upon microstructural change with thermal maturation) has also been the subject of extensive modern evaluation, with multiple studies highlighting the key influence of energy flux on the resultant charcoal microstructure. The ability to accurately quantify modern wildfire temperatures based upon novel Raman-charcoal analyses has not yet been attempted. Using Raman band width-ratios (i.e., FWHMRa) and accompanying geothermometric trends to natural wildfire charcoals, our results identify differences between microstructurally-derived fire temperatures compared to those recorded during the fire event itself. Subsequent assessments of wildfire energy flux over time indicate no dominant influence for the observed differences, due to the inherent complexity of natural fire systems. Further analysis within this study, regarding the influence of reference pyrolysis methodology on microstructural change, also highlights the difficulty of creating accurate post-fire temperature reconstructions. The application of Raman spectroscopy, however, to the quantification of relative changes in fire temperature continues to prove effective and insightful.